(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
People all over the world crave for peace. The educationists, politicians and the leaders of the world are trying their best to achieve world peace, but they face many problems. Many advanced countries of the world try to dominate the weaker ones, exploit them and capture their trade, thereby, decreasing the possibilities of world peace. Achieving world peace will remain a dream until they try to achieve peace at the local and global level. Hence, some measures should be taken to achieve peace at the national and international levels. It is here that the philosophy of Mahatma Gandhi shows us a ray of light for achieving peace. There is no way to peace, peace is the way.